PERANCANGAN SISTEM INFORMASI NILAI AKADEMIK SISWA PADA SMA NU 05 BRANGSONG BERBASIS WEB - adminjfik, adminjfik; Mila, Hasnan Afif; Mila, Vivi Nurcahyani (Jurnal Teknik Informatika dan Desain Komunikasi Visual, 2022)
SMA NU 05 Brangsong is one of the schools whose value processing is still done manually and of course by utilizing the use of Microsoft Office. However, it is not enough to overcome the various problems that are prone to occur. Problems that can be identified from the system that is currently running include delays in data input because it requires energy and relatively longer time. In addition, it is also prone to errors in the data that will be entered into the value record book. With that, the author wants to create a Webs-Based Information System for Student Academic Values at SMA NU 05 Brangsong using the Waterfall development method. This system was created with the aim of assisting teachers in the process of data collection, checking and making reports on student grade recaps and making it easier for students to view information related to their academic scores anytime, anywhere effectively and efficiently regardless of distance and time. In addition, this student academic value information system produces a system that can assist and facilitate teachers in the process of inputting student grade data, student data, teacher data, student attendance recap reports and other information related to SMA NU 05 Brangsong. This system is built using the MySQL database and the PHP programming language with HTML.